Factors Affecting the Hardness Characteristics of Microstructures in Gas Carburized Chromium Alloy Steels - et.al, Chang-Yeol Oh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We analyzed the factors affecting the gas carburizing microstructure of parts for constant velocity joints. Gas carburizing 0.15-0.20C1.13-1.14Cr chromium alloy steel used in automobile drive units is characterized by changing the properties of the carburizing layer in the depth direction. The experimental conditions were set to enable field application. The components of the specimen to be used for gas carburization were analyzed by X-ray fluorescence. Changes in the mechanical properties of the carburized layer were analyzed by micro-hardness, microstructure, and carburizing content. The gas carburization cycle was selected based on the simulation results. The characteristics change before and after carburization of two samples with different carbon and chromium content were analyzed. The carburization temperature that can be used for manufacturing automobile parts was 930°C, the carbon potential required for carburization was 0.90wt%, and the carbon potential required for diffusion was 0.75wt%. The inner and outer hardness values of the carburized layer satisfying the effective hardening depth of 550Hv were 400Hv-740Hv. In the case of 0.20C alloy steel, the effective hardening depth with a carburizing amount of 0.36wt% and a hardness of 550Hv was 1.467 mm. also in the case of 0.15C steel, its effective hardening depth was 0.746 mm. The simulation results for selecting the carburizing heat treatment conditions and the carbon change in the carburizing layer showed a similar trend. The carburizing structure related to hardness change was martensite. As a result of EPMA, SEM, and XRD analysis, the amount of carburized and the amount of martensite structure correlated, and the martensite increased as the amount of carburized increasing. As a result of EPMA analysis, the smaller the carburizing content the greater the depth of carburization. We intend to proceed with optimization conditions for mass production in connection with wear resistance and fatigue. It is expected that these results will contribute to the improvement of durability of automobile driving parts.